The advances in adjuvant therapy for tuberculosis with immunoregulatory compounds - Mi, Jie; Wu, Xueqiong; Liang, Jianqin (Frontiers in Microbiology, 2024)
Tuberculosis (TB) is a chronic bacterial disease, as well as a complex immune disease. The occurrence, development, and prognosis of TB are not only related to the pathogenicity of Mycobacterium tuberculosis (Mtb), but also related to the patient’s own immune state. The research and development of immunotherapy drugs can effectively regulate the body’s anti-TB immune responses, inhibit or eliminate Mtb, alleviate pathological damage, and facilitate rehabilitation. This paper reviews the research progress of immunotherapeutic compounds for TB, including immunoregulatory compounds and repurposing drugs, and points out the existing problems and future research directions, which lays the foundation for studying new agents for host-directed therapies of TB.